Estimation of individual cumulative ultraviolet exposure using a geographically-adjusted, openly-accessible tool. Issue 1 (December 2016) - Zhu, Gefei; Raber, Inbar; Sakshuwong, Sukolsak; Li, Shufeng; Li, Angela; Tan, Caroline; Chang, Anne
Abstract Background Estimates of an individual's cumulative ultraviolet (UV) radiation exposure can be useful since ultraviolet radiation exposure increases skin cancer risk, but a comprehensive tool that is practical for use in the clinic does not currently exist. The objective of this study is to develop a geographically-adjusted tool to systematically estimate an individual's self-reported cumulative UV radiation exposure, investigate the association of these estimates with skin cancer diagnosis, and assess test reliability. Methods A 12-item online questionnaire from validated survey items for UV exposure and skin cancer was administered to online volunteers across the United States and results cross-referenced with UV radiation indices. Cumulative UV exposure scores (CUES) were calculated and correlated with personal history of skin cancer in a case–control design. Reliability was assessed in a separate convenience sample. Results 1, 118 responses were included in the overall sample; the mean age of respondents was 46 (standard deviation 15, range 18 – 81) and 150 (13 %) reported a history of skin cancer. In bivariate analysis of 1:2 age-matched cases (n  = 149) and controls (n  = 298), skin cancer cases were associated with (1) greater CUES prior to first skin cancer diagnosis than controls without skin cancer history (242, 074 vs. 205, 379, p  = 0.003) and (2) less engagement in UV protective behaviors (p  < 0.01). In a multivariate analysis of age-matched data, individuals with CUES in the lowest quartile were less likely to develop skin cancer compared to those in the highest quartile. In reliability testing among 19 volunteers, the 2-week intra-class correlation coefficient for CUES was 0.94. We have provided the programming code for this tool as well as the tool itself via open access. Conclusions CUES is a useable and comprehensive tool to better estimate lifetime ultraviolet exposure, so that individuals with higher levels of exposure may be identified for counseling on photo-protective measures.